Psoriasis: Causes, Symptoms, Treatment, Effect on Quality of Life and Future Therapeutic Prospects: A Detailed Review - Vanshika Lohia (International Journal of Cell Biology and Cellular Functions, 2023)
Objective: This review’s objective is to provide an outline of how psoriasis is caused, what are its symptoms, what are the conventional methods being employed for treatment, and how future prospects can take over the conventional methods. We also aim to put light on how psoriasis is having a huge impact on people’s life quality in various fields of life and how this effect can be measured using instruments or questionnaires. Result: It was found that psoriasis can occur in any age group and has an equal effect on males and females. Environmental factors as well as hereditary ones are involved in causing psoriasis. Conventional methods are being used for the treatment and reduction of symptoms but none of the methods have been completely able to cure the disease, hence, there is a hope that nanotechnology can prove efficient. Patients with psoriasis experience substantial limitations in their quality of life affecting their work, social interaction, sexual activity, and confidence. Conclusion: Psoriasis is a non-curable disease but the recent developments in the field of nanotechnology have shown positive results and are expected to work together with topical therapies to cure the disease. Various nanostructures are in use and have proved efficient. But, apart from curing the symptoms, care has to be taken as to how the patients can have a normal life as other individuals and do not have to face social embarrassment as it strongly disturbs their confidence and happiness.
Keywords: Nanomedicine; Psoriasis; QoL Instruments; Quality of life; comorbidities; disease burden; psoriasis and depression